Serial assessment of somatic and cardiovascular development in patients with single ventricle undergoing Fontan procedure. (1st January 2021) - Granegger, M.; Küng, S.; Bollhalder, O.; Quandt, D.; Scheifele, C.; Drozdov, D.; Held, U.; Callegari, A.; Kretschmar, O.; Hübler, M.; Schweiger, M.; Knirsch, W.
Abstract: Background: The palliation of patients with single ventricle (SV) undergoing Fontan procedure led to improved long-term survival but is still limited due to cardiovascular complications. The aim of this study was to describe the somatic and cardiovascular development of Fontan patients until adolescence and to identify determining factors. Methods: We retrospectively assessed somatic growth, vascular growth of pulmonary arteries, and cardiac growth of the SV and systemic semilunar valve from 0 to 16 years of age using transthoracic echocardiography. The Doppler inflow pattern of the atrioventricular valve was quantified by E -, A-wave and E/A ratio. All data were converted to z-scores and analyzed using linear mixed effect models to identify associations with age at Fontan procedure, gender, and ventricular morphology. Results: 134 patients undergoing Fontan procedure at a median age of 2.4 (IQR 2.12 to 2.8) years were analyzed. A catch-up of somatic growth after Fontan procedure until school age was found, with lower body height and weight z-scores in male patients and patients with systemic right ventricles. An early time of Fontan procedure was favorable for somatic growth, but not for vascular growth. Cardiac development indicated a decrease of SV end-diastolic diameter z-score until adolescence. Despite a trend towards normalization, E -wave and E/A ratio z-scores were diminished over the entire period. Conclusions: There is a catch-up growth of somatic, vascular and cardiac parameters after Fontan procedure, which in our cohort depends on the time of Fontan procedure, ventricular morphology, and gender. Beside other factors, diastolic function of the SV remains altered. Highlights: There is evidence for a somatic catch-up growth after Fontan procedure palliation. It is impaired in infants with male sex and single right ventricle physiology. Earlier time of Fontan procedure is beneficial for vascular growth of pulmonary arteries. Later time of Fontan procedure is favorable for somatic growth. Cardiac growth and diastolic function remains altered until adolescence.